Manfaat Donor Darah dalam Meningkatkan Kesehatan Masyarakat: Studi Kasus Desa Kampung Baru, Kelurahan Galang Baru, Kota Batam - Alya Rahmaditya Arfan; Astrid Siska Pratiwi; Deasy Ovi Harsachatri (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
Blood donation is a crucial activity in maintaining the availability of blood for transfusion; however, awareness of the importance of blood donation still needs to be increased in various communities, including Desa Kampung Baru, Kelurahan Galang Baru, Kota Batam. This study aims to investigate the effectiveness of education about the benefits of blood donation in increasing community participation in the area. The education was conducted through interactive lectures and question-and-answer sessions at the Desa Kampung Baru Community Hall. The educational material included the benefits of blood donation for both recipients and donors, the blood donation procedure, and the requirements to become a donor. The study results showed an increase in community participation in blood donation activities after the education was conducted. More residents of Desa Kampung Baru now understand the benefits of blood donation in saving lives, reducing the risk of heart disease, and renewing red blood cells in the body. Nonetheless, further monitoring and evaluation efforts are needed to ensure the sustainability of participation in blood donation in the future. This study significantly contributes to increasing public awareness of the importance of blood donation and ensuring the availability of blood supplies to support overall public health.